Competing by design the power of organizational architecture - Nadler, David A.; Tushman, Michael L. 1943- (Oxford Univ. Press, 1997)
This book offers managers a systematic means of analyzing their organizations and, in turn, building integrated organizations to achieve sustainable competitive advantage. It leads managers through the process of designing new and more flexible organizations that will provide a firm's competitive edge into the next millennium
Keywords: Changement organisationnel - Gestion; Changement organisationnel; Concurrence; EFECTIVIDAD ORGANIZACIONAL; Efficacité de l'organisation; Efficacité organisationnelle; Entreprises - Réorganisation - Gestion; Organisatiestructuur; Organisatieverandering; Organisation de l'entreprise; Organizational effectiveness; Organizational change -- Management; Corporate reorganizations -- Management; Competition; Management; Organisationsgestaltung; Organisationsentwicklung; Wettbewerbsfähigkeit; Organisationswandel; Unternehmen; Strategisches Management; Organisationsstruktur; Unternehmensentwicklung